1999
DOI: 10.1017/s0954579499001923
|View full text |Cite
|
Sign up to set email alerts
|

Implications of attachment theory for developmental psychopathology

Abstract: Bowlby's attachment theory is a theory of psychopathology as well as a theory of normal development. It contains clear and specific propositions regarding the role of early experience in developmental psychopathology, the importance of ongoing context, and the nature of the developmental process underlying pathology. In particular, Bowlby argued that adaptation is always the joint product of developmental history and current circumstances (never either alone). Early experience does not cause later pathology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
353
0
27

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(390 citation statements)
references
References 5 publications
10
353
0
27
Order By: Relevance
“…1 When a parent deploys, the separation of parent and child influences the child's current and future development. 2,3 Similar effects of child separation from a parent have been documented in a variety of settings, including divorce and parental incarceration, migration, or hospitalization. [4][5][6][7][8][9] In a 2006 survey of military spouses, 20% of parents reported that their children coped poorly during military deployments.…”
mentioning
confidence: 82%
“…1 When a parent deploys, the separation of parent and child influences the child's current and future development. 2,3 Similar effects of child separation from a parent have been documented in a variety of settings, including divorce and parental incarceration, migration, or hospitalization. [4][5][6][7][8][9] In a 2006 survey of military spouses, 20% of parents reported that their children coped poorly during military deployments.…”
mentioning
confidence: 82%
“…10,11 Children can be exposed to violence across multiple socio-ecological contexts including in the neighborhood, school, and home. 12 In the home, child maltreatment, including neglect, as well as physical and psychological aggression, has consistently been associated with elevated aggressive and externalizing behavior in children and youth.…”
mentioning
confidence: 99%
“…20 Preterm infants, especially those born with lower birth weights or greater medical risks, seem to be at risk for developing insecure attachments. [21][22][23] Insecure attachment is a nonspecific risk for later psychopathological conditions, [24][25][26] whereas attachment security is related to subsequent social competence and empathy. [27][28][29] The association between maternal grief resolution and attachment has been explored among children with diagnosed chronic medical conditions or disabilities by using the Reaction to Preterm Birth Interview (RPBI).…”
mentioning
confidence: 99%
“…34 Since initial validation, associations between RPBI grief resolution and the quality of parent-child interactions or attachment have been demonstrated for multiple clinical samples, including children with Down syndrome, autism, cerebral palsy, epilepsy, and phenylketonuria, [31][32][33][35][36][37][38] but has not been explored for premature infants. Because feelings of grief are common among mothers of preterm infants 4,6 and because infant attachment predicts children's later social/emotional development, 25 it is important to identify associations between maternal grief regarding preterm birth and attachment, so that vulnerable mother-infant dyads can be identified and supported.…”
mentioning
confidence: 99%